1962
DOI: 10.1111/j.1476-5381.1962.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

NEUROTOXIC SYNDROME PRODUCED IN CHICKENS BY A CYCLIC PHOSPHATE METABOLITE OF TRI‐o‐CRESYL PHOSPHATE—A CLINICAL AND PATHOLOGICAL STUDY

Abstract: A clinical and neuropathological comparison was made between chickens poisoned with tri-o-cresyl phosphate and those treated with the major cyclic phosphate metabolite of tri-o-cresyl phosphate. Ataxia was evident with both materials, and the degree of peripheral neuropathy increased with higher doses of these agents. Morphological changes were evident with the onset of symptoms and increased in number as the neurological signs progressed. Demyelination of the spinal cord following administration of the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Its very low solubility in aqueous and even in organic solvents is reminiscent of the arylphosphates and might suggest that conversion in a like manner might occur to produce a toxic product (Baron, Bennett, and Casida, 1962). The indications noted here that transfer of toxic material in doses high enough to produce paralysis and spinal tract changes can occur, albeit mild, suggest the possibility of a toxic (and more potent) conversion product being transferred from one animal to another.…”
Section: Discussionmentioning
confidence: 77%
“…Its very low solubility in aqueous and even in organic solvents is reminiscent of the arylphosphates and might suggest that conversion in a like manner might occur to produce a toxic product (Baron, Bennett, and Casida, 1962). The indications noted here that transfer of toxic material in doses high enough to produce paralysis and spinal tract changes can occur, albeit mild, suggest the possibility of a toxic (and more potent) conversion product being transferred from one animal to another.…”
Section: Discussionmentioning
confidence: 77%
“…The agent most commonly discussed as being responsible for aerotoxic syndrome is tri-o-cresyl phosphate, though this has not yet been proven. [81,82] Reaction of butyrylcholinesterase with 2-(o-cresyl)-4H-1,2, 3-benzodioxaphosphoran-2-one results in a unique, phosphobutyrylcholinesterase adduct [83,84] which is a convenient marker for in vivo exposure to tri-o-cresyl phosphate. [2,78,79] Tri-o-cresyl phosphate itself is not toxic.…”
Section: Proteolysis Of Labelled Proteinbutyrylcholinesterase Phosphatementioning
confidence: 99%
“…Injection of high doses of 2-(o-cresyl)-4H-1,2,3-benzodioxaphosphoran-2-one into chickens causes ataxia and demyelination of nerves in the spinal cord which are typical symptoms of organophosphate-induced delayed neuropathy. [81,82] Reaction of butyrylcholinesterase with 2-(o-cresyl)-4H-1,2, 3-benzodioxaphosphoran-2-one results in a unique, phosphobutyrylcholinesterase adduct [83,84] which is a convenient marker for in vivo exposure to tri-o-cresyl phosphate. Purification of butyrylcholinesterase from exposed serum using ion-exchange chromatography (Q-Sepharose, at pH 4) and procainamide affinity chromatography, followed by pepsin digestion and enrichment/ concentration of the phospho-peptide using titanium-oxide affinity chromatography (Titansphere, TiO 2 ) creates a preparation from which as little as 0.05% phosphorylated butyrylcholinesterase can be detected using matrix-assisted laser desorption/ionization TOF-MS. [85] Testing of the serum from random airline passengers immediately after flying has shown that approximately 50% have phosphorylated butyrylcholinesterase, despite the fact that those passengers showed no signs of toxicity.…”
Section: Proteolysis Of Labelled Proteinbutyrylcholinesterase Phosphatementioning
confidence: 99%
“…The internal dynamics of these compounds within a medium as complex as the human body, with a variety of sources (mainly lungs and skin) and sinks, is far from being understood. The liver is the main organ for eliminating TCP; unfortunately the first metabolic product, cresyl saligenin phosphate (2-(ocresyl)-4H-1,3,2-benzodioxaphosphorane-2-one (CBDP) is the metabolite of tri-o-cresyl phosphate) appears to be even more toxic than TCP itself [17][18][19], further complicating the dynamics. 5 High temperatures are encountered within jet engines.…”
Section: Hazards From Inhalationmentioning
confidence: 99%
“…Having achieved a largely accident-free state, attention can now turn to ensuring wellbeing on board. 18 In order to obviate the possibility of inhaling TCP (and any other substance of comparable toxicity), the following options would appear to be available, in order of decreasing difficulty:…”
Section: Possible Technical Solutionsmentioning
confidence: 99%